2004
DOI: 10.1111/j.1523-1755.2004.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diseases in maintenance hemodialysis patients: Results of the HEMO Study

Abstract: The HEMO Study identified IHD to be a major cause of cardiac hospitalizations and cardiac deaths. Future strategies for the prevention of cardiac diseases in the maintenance hemodialysis population should focus on this entity. Although high-flux dialysis did not reduce all-cause mortality, it might improve cardiac outcomes. This hypothesis needs to be further examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
367
2
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(396 citation statements)
references
References 20 publications
16
367
2
11
Order By: Relevance
“…Zoccali et al 7 in a study of 254 hemodialysis patients, Rakhit et al 35 in a study that included 176 patients with CKD stages 4 and 5 on conservative treatment or dialysis, and Cheung et al 22 in the HEMO multicenter study, described a similar result in the final model of Cox multivariate analysis.…”
Section: Siqueira Et Al Doppler Echocardiogram In Hemodialysis Patientssupporting
confidence: 50%
See 1 more Smart Citation
“…Zoccali et al 7 in a study of 254 hemodialysis patients, Rakhit et al 35 in a study that included 176 patients with CKD stages 4 and 5 on conservative treatment or dialysis, and Cheung et al 22 in the HEMO multicenter study, described a similar result in the final model of Cox multivariate analysis.…”
Section: Siqueira Et Al Doppler Echocardiogram In Hemodialysis Patientssupporting
confidence: 50%
“…HEMO and AURORA studies, showed rates of less than 50% of mortality due to heart disease in the dialysis population 22,23 . These results confirm that CVD remain the leading cause of morbidity and mortality in hemodialysis patients.…”
Section: Survival Function Censoredmentioning
confidence: 99%
“…The protocols used for the collection and validation of outcome data have been previously described in detail (12)(13)(14). The primary outcome of the HEMO Study was all-cause mortality.…”
Section: Follow-up and Outcomesmentioning
confidence: 99%
“…Acute myocardial injury is a leading cause of hospitalisation and death in the dialysis population (9.8-16 per 100-patient years), and cardiac troponins are among the most frequently requested tests in this group [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%